Neosufisme dan Kesadaran Beragama Kaum Urban - Putri Rezeki Rahayu (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2022)
The modernization era, with its advances in science and technology, has had an impact on the survival of society. One of the consequencesis the phenomenon of urbanization, which is the movement of rural peopletocities in searchof a more advanced urban life. Because of technological advancements, today's society has separated spiritual and socialneeds. As a result, urban communities have less spirituality than rural communities, which still have strong religiousnuances. This study aims to investigate the meaning of Neosufism in the live sofurbanites in order to educate them about spirituality in light of theincreasingly complex problemsthaturbanitesface as a result of technological advancements. This researchutilizes a literature review method, obtaining articles related to topics within the last 5 years. The meaning of Neosufism can be defined as one of the Sufi schools that combines a social perspective with a spiritual or religious perspective. In thiscase, it is capable of assisting urbanites by raising religious awareness and making religion not only a symbol but also anideology in living life to calm the body and spirit from the problems they face because the main focus is the spirit of the vitality of Muslim socio-moral reconstruction.